Modelos de programación entera para el problema de aignación de horarios en cursos universitarios; Integer programming model for the timetabling problem in university courses - Carlos Andrés Arango Londo\~no; Heriberto Felizzola Jiménez; Andres Mauricio Hualpa Zu\~niga; Paula Zuranny Gómez Martínez; Carlos Felipe Mora Garzón (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– Timetabling scheduling is classified as a combinatorial problem for which there are multiple solution alternatives, including the integer programming. However, the modeling of operational rules and the size of real problems makes its use not common compared to other techniques. This article proposes an integer programming model (IP) model, which addresses the scheduling problem made up of variables associated with time slots, subject and assigned teacher. Parameters such as the number of minimum and maximum time slots to be taught by the teacher, time slot time, teacher availability, available classrooms and estimated cost of dissatisfaction generated by the assigned schedule are also included. Seven hard and seventeen soft constraints are integrated into the model, which provide higher quality to the final schedule solution. The IP model is validated with a global objective function, in which experiments, and results obtained in real instances of the Universidad de la Salle (ULS) are reported. The new solution approach offers improvements in the final schedules, as well as the interaction with the users during its construction. Finally, in the conclusions of the work, the design and development of a system that provides support for decisions is discussed, referencing suggestions for future developments.
Keywords: C61; 330; Timetabling; integer programming; classroom assignment